Stability analysis on tower crane foundation using finite element method - Faizatul Shima,; Anuar Kasa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Currently, the construction of high-rise buildings is increasing as the modernization of the city. Especially in the heart of Kuala Lumpur City, construction is more focused on the construction of high-rise buildings due to over-crowded areas. To meet demand due to the activity, the number of tower cranes brought into Malaysia has increased. The tower crane is used to lift construction items and requires a solid base to ensure tower crane stability. Analysis obtained from the Department of Occupational Safety and Health (DOSH), the rate of accidents involving in particular the use of cranes tower cranes occurred due to the failure of the crane foundation. The main objective in carrying out this project is to ensure the stability of the foundations for ensuring the safe use of tower cranes in reducing accident site, determine the calculation of the basic design of the site and the last one is to analyze the stability of the soil through the interaction between the soil and the basic structure of the site. Design calculations from qualified engineers as well as engineering software for analysis tests are an important element in the success of this research project. Among the parameters required are ground properties information for the installed tower cranes, engineering drawings for tower crane structure and Plaxis 3D computer software for analysis purposes. The implication of this project is to achieve the department’s quality policy in providing and maintaining a quality, safe and healthy work and system without any harm and risk.